Objetos de aprendizagem no ensino de matemática e física: uma proposta interdisciplinar - Sousa, Edvaldo Vale de (2010)
This research aimed to see how an approach based on the use of "Learning Objects", designed in the context of physics can promote the learning of the mathematical concept of function and representations of this concept in high school students and what benefits a computing environment that based on simulations of physical phenomena related to kinematics can bring to a sequence of didactic methodology that takes these students to build that concept. To achieve this goal have been developed three activities approaching interdisciplinary the subjects: a mobile frame; uniform motion (MU); uniformly varied motion (MUV) functions of the 1st and 2nd grade. The activities included simulations on "Learning Objects" and were prepared under conditions of didactic engineering in conjunction with some guiding principles as the effects of didactic contract in relation learner / knowledge / teacher, the student's analysis of the actions proposed by the Theory of Didactic Situations the development and structuring of mathematical problem-situations by Theory Records Offices, and the interdisciplinary aspects between physics and mathematics fields. The subjects of this investigation were the first graders of high school in a school on the outskirts of Sao Bernardo do Campo. The trial was performed in ten sessions that have favored the inclusion digital of 34 students divided into two classes: class A (separated into ten pairs) and class B (separated in seven pairs). The results presented in the achievements of students corroborate the use of "Learning Objects", designed in the context of physics as a technology that can be used in an interdisciplinary approach to the disciplines of physics and mathematics, since they, beyond to motivate students for the appearance of dynamic and interactive simulations that bring reality situations, also present the records of representation in graphical form and algebraic situations, problems intrinsic to the "Learning Objects" that can help in understanding the relationship between the empirical and theoretical. As a result of the interaction student / computer, the students succeeded in completing the graphical programming speed of the phenomenon which determined the constructionist approach of the students in programming situation where sometimes the cycle repeated description-execution-reflection-debugging-description so to achieve the desired result. The use of "Learning Objects" in conjunction with the following methodology and didactic content related interdisciplinary approach led to meaningful learning with the following topics: the meaning and relationship between the coefficients in office hours in MU and MUV and functions 1st and 2nd grade, description of the representation of functions in the records tabular, algebraic and graphic, interpretation and natural language passage record for the record through the algebraic structure of the mathematical phenomenon intrinsic to the problem situation